2022
DOI: 10.33222/jumlahku.v8i1.1493
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Hipnoterapi Terhadap Kecemasan Belajar Matematika Dengan Pembelajaran Jarak Jauh

Abstract: Tujuan penelitian ini adalah agar siswa tidak mengganggap bahwa pelajaran Matematika merupakan mata pelajaran yang tidak menyenangkan, yang meninmbulkan kecemasan dan bahkan ada rasa takut bagi siswa setiap akan bertemu dengan pembelajaran matematika. Metode penelitian ini menggunakan penelitian kuantitatif dengan metode eksperimen dengan design penelitian one group pretest-postest, design. Populasi dalam penelitian adalah siswa SDN Sukamulya 2 yang berjumlah 20 orang, dengan sampel 10 orang. Penelitian ini ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A pandemic is a disease outbreak that spreads very quickly to people and occurs in almost all regions of the world, covers a very wide range, and crosses international boundaries (Masrul, 2020) and (Suryaman, Yuliardi, & Anwar, 2022). Corona viruses are a large family of viruses that cause disease in humans and animals.…”
Section: Previous Research Related To Hypnotherapy Are Budiman Effect...mentioning
confidence: 99%
See 1 more Smart Citation
“…A pandemic is a disease outbreak that spreads very quickly to people and occurs in almost all regions of the world, covers a very wide range, and crosses international boundaries (Masrul, 2020) and (Suryaman, Yuliardi, & Anwar, 2022). Corona viruses are a large family of viruses that cause disease in humans and animals.…”
Section: Previous Research Related To Hypnotherapy Are Budiman Effect...mentioning
confidence: 99%
“…In general, Hypnotherapy is closely related to the work activities of the human brain. This activity is very diverse in every condition in accordance with human brain waves (Sugiarso, 2013: 2), (Lisnawati, 2020), and (Suryaman, Anwar, Hadiana, & Sutarna, 2022). From some of the above understanding, it can be concluded that Hypnotherapy is a treatment technique that uses the human subconscious which is generally related to the work activities of the human brain to cure diseases experienced by humans both physically and psychologically and focuses the process on the client himself.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with (Basith et al, 2021) that Cognitive indicators dominate student academic stress: Academic achievement or academic achievement causes negative emotions in the form of anxiety, fear, and full of hope of graduating. Academic situations such as exams and learning processes cause anxiety in students (Hidayah, N., & Atmoko, 2014); Subjects (Suryaman, Anwar, Hadiana, & Sutarna, 2022); Learning System (Suhendro & Agustina, 2022); Personal, family, social and institutional (Kartika, 2020). Anxiety experienced by a person is the reason for making decisions for himself in the future (Hanurawan, 2018).…”
Section: Introductionmentioning
confidence: 99%